Principal Supervision Management to Improve Teacher Professionalism - Ilyas, Ilyas (Riviera Publishing, 2024)
This research is a field research through a descriptive qualitative approach. The data was obtained from the head of the madrasah, along with the curriculum waka and teachers. The method used in collecting data through interviews, documentation and observation of the results obtained through supervision used by the head of the madrasah by the principal can run in reality, for teachers to be more serious to carry out their duties as teachers and full of responsibility. The results are very good, teachers have received input from the head of the madrasah before teaching, they have prepared methods, media and strategies so that learning is successful, so that teachers can become professionals. Teachers are given guidance through trainings that are carried out at least twice in two semesters, whether it is through a trainer, then MGMP will also receive rewards in the form of awards.